The Switzerland Phenomenon – An Example of Sustainable Development of a Nation - Suvorov, Nikolay; Suvorova, Irina (European Journal of Sustainable Development, 2017)
The main concepts and principles of development employed in Switzerland at the nation survival stages are considered. To ensure sustainable development, a scientific approach is used to suggest methods for forming a new Man capable of addressing problems and solving tasks not only at the development-survival stages, but also at the nation welfare stage. Keywords: survival of a nation, nation’s welfare, sustainable development, new Man